The Territorial and Sectoral Trends in the Industry of the Eurasian Economic Union - Chasovsky, Vladimir I.; Katrovsky, Alexander P. (International Journal of Economics and Financial Issues, 2015)
The article examines trends and changes in the territorial and sectoral structure of the industry of the Eurasian Economic Union, the patterns of transforming the industrial systems into more effective integrated centres under the transitive conditions. The national industry transformation is associated with the use of mechanisms of creating the industrial and integration structures through the single organisational and production modules capable of efficiently connecting and transforming the elements of the national industrial structure into transnational competitive production units. These units are spatial entities, such as clusters and other market-based forms of production that are a kind of ‘growth nodes' and act as elements of the emerging new regional industry framework. Keywords: industry, transformational economy, transnational reproductive pole, international integration, growth nodes, industrial policy JEL Classifications: F6; L5; R12